Penilaian Tingkat Kematangan Sistem Pengelolaan Sampah Cerdas: Studi Kasus pada PT.XYZ - Dimas Ahda Sabila; Yekti Wirani; Yudho Giri Sucahyo (The Indonesian Journal of Computer Science, 2025)
Facing increasingly complex urban waste management challenges, this study evaluates the maturity level of Smart Waste Management implementation in Indonesia, with a case study of PT. XYZ. In Indonesia, the implementation of Smart Waste Management is still in its early stages, yet its urgency continues to grow due to increasingly complex urban waste problems. The study examines Smart Waste Management System maturity levels and identifies key implementation factors, utilizing both qualitative and quantitative approaches. Assessment results indicate an average maturity level of 3-Integrated out of 5-Smart, with variations across different processes. Key areas requiring enhancement include governance, social, technological, and economic dimensions. This evaluation provides valuable insights for improving operational efficiency, environmental impact, and community service delivery in waste management. The findings contribute to understanding SWMS implementation challenges and opportunities, offering strategic recommendations for advancing sustainable waste management practices in Indonesia.